2′-Fluoro-c-di-GMP as an oral vaccine adjuvant. Issue 71 (16th December 2019) - Li, Jia; Lee, Rhonda Kuo; Chen, Wangxue; Yan, Hongbin
Abstract : 2′-F-c-di-GMP was synthesized through the modified H-phosphonate chemistry. 2′-F-c-di-GMP was found to be an effective mucosal vaccine adjuvant, both intranasally and orally. Abstract : Bis-(3′–5′)-cyclic dimeric 2′-deoxy-2′-fluoroguanosine monophosphate (2′-F-c-di-GMP) was synthesized through the modified H-phosphonate chemistry. Oral immunization of C57BL/6 mice with Helicobacter pylori cell-free sonicate extract adjuvanted with 2′-F-c-di-GMP led to the production of antigen-specific antibodies in feces and sera, and lowered bacterial counts in the stomach upon post-vaccination infections in immunized mice. Similarly, oral vaccination of BALB/c mice with flagillin proteins from Clostridium difficile and Listeria monocytogenes adjuvanted with 2′-F-c-di-GMP led to production of antigen-specific antibodies both systemically and mucosally. The adjuvanticity of 2′-F-c-di-GMP is associated with the enhanced induction of interferon γ. These results demonstrated the excellent oral adjuvanticity of 2′-F-c-di-GMP.